Strategi Pengelolaan Limbah Medis Padat Pada UPTD Puskesmas Lampahan yang Berdampak Pencemaran Lingkungan - Endang Saruni; Abdul Malik; Zulfikar (Jurnal Serambi Engineering, 2024)
The aim of the research is to get an overview of the types, determine management factors, get recommendations to determine the right strategy in order to reduce environmental pollution due to solid medical waste at the UPTD of the Lampahan Community Health Center and in the community environment. Data analysis was carried out using several parameters through statistical tests and discussed quantitatively descriptively. The results of the research showed that to identify types of solid medical waste, syringes, Nald heating, gauze, infusion bottles, hand scoops, medicine bottles, masks, abocaths, needles, used plasters, urine catheters, urine bags and basturi were identified. Several factors include the knowledge of officers regarding the management and handling of solid medical waste which still varies greatly, especially in the field of health services, such as in the ER, inpatient rooms, drug distribution (pharmacies) and midwives who do not yet understand how to actually manage medical waste. Another risk factor occurs in community groups regarding their ability to act regarding the presence of solid medical waste originating from the Puskesmas environment, including actions in handling it. The strategy that will be used as a recommendation in managing solid medical waste is through increasing the capacity of human resources, increasing support for budget allocations, increasing monitoring of officer compliance in using PPE, and proposals for procuring waste management facilities as well as strengthening cooperation with third parties, licensing related to storage, packaging, labeling and providing waste symbols.